Mainstreaming Green Investment in Sharia Securities in Indonesia (Case Study of North Sumatra Province) - Syahputra, Angga; Nurhayati, Nurhayati; Soemitra, Andri (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2025)
Purpose: The purpose of this study is to explore the mainstreaming of green investment in Islamic securities in North Sumatra. This research focuses on identifying key aspects, challenges, solutions, and priority strategies to promote green investment, particularly in sharia-compliant stocks. Given the global trend of increasing green investment, which reached 2.5 trillion USD by 2021, this study aims to analyze the role of green investment in supporting sustainable economic development, especially in North Sumatra, where no issuers are currently included in the ESG index despite having 12 IPO issuers, 9 of which are sharia stocks.Design/methodology: This research utilizes the Analytical Network Process (ANP) method to systematically identify the factors influencing green investment in Islamic securities. The study examines aspects such as profit and risk, the primary challenges investors face, and possible solutions to mitigate financial risks.Findings: The findings reveal that profit and risk considerations are key factors influencing green investment in Islamic securities. The main challenge identified is the uncertainty of financial risk, which deters potential investors. The priority solution to address this issue is implementing effective risk management strategies to reduce investment uncertainty. Additionally, increasing awareness and education on green investment can help improve investor confidence and participation.Practical implications: The implications of this research emphasize the importance of various efforts to provide an understanding of the importance of green investment in Islamic stocks to various parties so that the mainstreaming of green investment in North Sumatra can be achieved.Originality/Value: The originality of this study lies in its focus on an under-researched area, offering practical recommendations for integrating sustainability principles into Islamic financial markets.